Identification of some soluble esterases of the carrot (Daucus carota I.) - Carino, Lourminia Almeda (2012)
Substrate and inhibitor specificities have been used to classify esterases. The purpose of this work was to determine the substrate and inhibitor specificities of the esterases in an aquous extract of lyophilyzed carrots. Esterase activity was determined manometrically at 37°C. The optimum pH of the carrot esterases with several substrates varied from 6.8 to 7.2, and a pH of 7.2 was used in this study. The carrot extract hydrolyzed acetyl, propionyl and butyryl esters of phenol, 2-naphthol-6-SO₃Na and glycerol. As the acyl chain length was increased, activity decreased. Long-chain naphthyl esters and triolein were not hydrolyzed, which suggested the absence of lipase in the extract. Lack of activity with choline esters indicated the absence of cholinesterases. EDTA did not exhibit appreciable activation of carrot esterases. The effect of parathion, diisopropyl phosphorofluoridate (DFP) and tetraethyl pyrophosphate (TEPP) at various concentrations on the rate of hydrolysis of the acetyl, propionyl and butyryl esters, of phenol, 2-naphthol-6-SO₃Na and glycerol indicated the presence of six esterases. Inhibitor and substrate specificities of five esterases were similar to carboxylesterases (EC 3.1.1.1). The sixth esterase was similar to arylester as e (EC 3.1.1.2). An enzyme hydrolyzing DFP and TEPP was suggested in the carrot extract. === Graduation date: 1968